Value acquisition, value co-creation: The impact of perceived organic grocerant value on customer engagement behavior through brand trust - Yu, Weiping; He, Mingli; Han, Xiaoyun; Zhou, Jun (Frontiers in Psychology, 2022)
Affected by COVID-19, there is a growing trend toward healthy lifestyles and organic food consumption. The literature on organic foods focuses on the factors that influence buying behavior. A thriving organic business requires both sustained consumption and consumer contributions beyond the purchase – customer engagement behavior. The purpose of this study is to examine the factors that may drive member customers to engage with organic grocerants. This study surveyed 280 Chinese member customers of an organic grocerant to explore how to drive customer engagement behavior. Based on value co-creation theory and the customer engagement literature, this study proposed a “value acquisition - value co-creation” framework to explore the relationship between perceived value, brand trust and customer engagement behavior. The results show that emotional and social value can directly and effectively motivate customer engagement behavior in organic grocerants. However, consumers’ perceived quality value and price value will not directly affect customer engagement behavior but instead indirectly affect it through brand trust. Furthermore, improving the perceived value of emotion, quality and price can strengthen brand trust in organic grocerants. The study confirms that brand trust is critical to organic grocerant and customer engagement. Our findings provide a new perspective for understanding the relationship between the value customers receive from organic food consumption and value co-creation through customer engagement behavior.